Efficacy of three innovative bacterin vaccines against experimental infection with Mycoplasma hyopneumoniae - Anneleen Marguerite Filip Matthijs (Veterinary Research, 2019)
Abstract New vaccine formulations that include novel strains of Mycoplasma hyopneumoniae and innovative adjuvants designed to induce cellular immunity could improve vaccine efficacy against this pathogen. The aim of this experimental study was to assess the efficacy of three experimental bacterin formulations based on M. hyopneumoniae field strain F7.2C which were able to induce cellular immunity. The formulations included a cationic liposome formulation with the Mincle receptor ligand trehalose 6,6-dibehenate (Lipo_DDA:TDB), a squalene-in-water emulsion with Toll-like receptor (TLR) ligands targeting TLR1/2, TLR7/8 and TLR9 (SWE_TLR), and a poly(lactic-co-glycolic acid) micro-particle formulation with the same TLR ligands (PLGA_TLR). Four groups of 12 M. hyopneumoniae-free piglets were primo- (day (D) 0; 39 days of age) and booster vaccinated (D14) intramuscularly with either one of the three experimental bacterin formulations or PBS. The pigs were endotracheally inoculated with a highly and low virulent M. hyopneumoniae strain on D28 and D29, respectively, and euthanized on D56. The main efficacy parameters were: respiratory disease score (RDS; daily), macroscopic lung lesion score (D56) and log copies M. hyopneumoniae DNA determined with qPCR on bronchoalveolar lavage (BAL) fluid (D42, D56). All formulations were able to reduce clinical symptoms, lung lesions and the M. hyopneumoniae DNA load in the lung, with formulation SWE_TLR being the most effective (RDSD28–D56 −61.90%, macroscopic lung lesions −88.38%, M. hyopneumoniae DNA load in BAL fluid (D42) −67.28%). Further experiments raised under field conditions are needed to confirm these results and to assess the effect of the vaccines on performance parameters.